Dominant discourse, orientalism and the need for reflexive HRM: skilled Muslim migrants in the German context. Issue 8 (28th April 2017) - Mahadevan, Jasmin; Kilian-Yasin, Katharina
Abstract: Muslim immigrants and their descendants are a relevant minority group in many Western European countries, and HRM needs to concern itself with this diversity. To better understand the HR requirements with regard to this group, we analyse HR discourse on skilled Muslim migrants in a German research company. We argue that dominant macro-societal discourse based on Orientalist thought might result in pre-reflexive HRM that creates inferior Muslim Others . Based on this finding, we establish the need for reflexive HRM. Our study contributes to International HRM (IHRM) literature in three ways. Firstly, it highlights the need for HRM reflexivity when managing the Muslim diaspora in the West. Secondly, it extends the analytical scope of HRM as discourse to the macro-societal level. Thirdly, it uncovers Orientalist thought in HRM discourse and traces it to specific IHRM issues, such as managing Muslim talent, thereby making reflexivity concise and manageable in theory and practice.